2016
DOI: 10.4103/0971-9784.179625
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, microbiological profile of nosocomial infections, and their antibiotic resistance patterns in a high volume Cardiac Surgical Intensive Care Unit

Abstract: Background:Nosocomial infections (NIs) in the postoperative period not only increase morbidity and mortality, but also impose a significant economic burden on the health care infrastructure. This retrospective study was undertaken to (a) evaluate the incidence, characteristics, risk factors and outcomes of NIs and (b) identify common microorganisms responsible for infection and their antibiotic resistance profile in our Cardiac Surgical Intensive Care Unit (CSICU).Patients and Methods:After ethics committee ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
47
1
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 19 publications
8
47
1
4
Order By: Relevance
“…Several studies reported the prevalence of Enterobacteriaceae as causative of nosocomial infections, in India; a recent study revealed that Enterobacteriaceae are the most frequently isolated in hospitals (Sahu et al, 2016), this concur with the high frequency of Enterobacteriaceae (59%) revealed in the present study. In the present study, the proportion of surfaces contamination with MDR-E was 61%.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Several studies reported the prevalence of Enterobacteriaceae as causative of nosocomial infections, in India; a recent study revealed that Enterobacteriaceae are the most frequently isolated in hospitals (Sahu et al, 2016), this concur with the high frequency of Enterobacteriaceae (59%) revealed in the present study. In the present study, the proportion of surfaces contamination with MDR-E was 61%.…”
Section: Discussionsupporting
confidence: 91%
“…In these series of strains, all Enterobacteriaceae presented high level resistance to most antibiotics tested, this results have been likely previously reported in several studies worldwide, either clinical or surfaces isolates (Karlowsky et al, 2003;Touati et al, 2010;Sahu et al, 2016;Jalapoor, 2011).…”
Section: Discussionsupporting
confidence: 83%
“…Surgical source control in patients with severe abdominal sepsis is critical to patient survival [26], and is especially important with the current increase in antibiotic resistance in surgical ICU patients [27], as well as suboptimal practices related to the use of antibiotics [28]. Novel therapeutic approaches, such as NPWT-I, that allow for rapid source control without the use of drugs, appear to be valuable addition to traditional therapeutic strategies for management of contaminated abdominal cavities.…”
Section: Discussionmentioning
confidence: 99%
“…In respiratory tract infections (n=29), Klebsiella (9), Acinetobacter (8) and CoNS (4) were the pathogens frequently isolated.…”
Section: Pneumoniamentioning
confidence: 99%
“…8 Because of widespread and irrational use of antibiotics, antibiotic resistance has increased exponentially causing grave prognosis in the management of infectious diseases. 2 The study results also indicate the same.…”
Section: Abdominal Infectionsmentioning
confidence: 99%